PEMBERDAYAAN WARGA DENGAN PELATIHAN DAN PEMBENTUKAN POSYANDU LANSIA BAGI KADER DUSUN WATES, PANGGANG, GUNUNG KIDUL, YOGYAKARTA - Scholastica Fina Aryu Puspasari (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2026)
Elderly people in Kemiri, Gunung Kidul access health services when getting sick. Based on preliminary study, 200 elderly people haven’t received elderly posyandu services and cadres have not been able to provide health services for the elderly. The solution offered is initiate, accompany and supervise elderly posyandu, train cadres to organize elderly posyandu, and provide facility. Training and formation of elderly posyandu was carried out on Thursday, December 21, 2023. The pretest results showed that 48% of cadres didn’t have adequate knowledge to manage elderly posyandu. The material provided included Posyandu knowledge and the role of Posyandu cadres. The post-test showed that 58% of cadres had adequate knowledge to manage elderly posyandu with a good level of knowledge and 37% were very good. The next stage is mentoring stage by providing direct services to elderly and providing facilities to support the posyandu. From the evaluation results, it was concluded that there was an increase in knowledge from average value of 6.5 to 8.4, elderly posyandu services had been implemented with 5 tables, cadres were able to provide basic health check-up services. Suggestion: hamlet managers continue to collaborate with the Health Center Team to get support in implementing elderly posyandu